2021
DOI: 10.5194/gmd-14-7021-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of global EMEP MSC-W (rv4.34) WRF (v3.9.1.1) model surface concentrations and wet deposition of reactive N and S with measurements

Abstract: Abstract. Atmospheric pollution has many profound effects on human health, ecosystems, and the climate. Of concern are high concentrations and deposition of reactive nitrogen (Nr) species, especially of reduced N (gaseous NH3, particulate NH4+). Atmospheric chemistry and transport models (ACTMs) are crucial to understanding sources and impacts of Nr chemistry and its potential mitigation. Here we undertake the first evaluation of the global version of the EMEP MSC-W ACTM driven by WRF meteorology (1∘×1∘ resolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 68 publications
(77 reference statements)
5
24
0
Order By: Relevance
“…For the trend studies presented in Theobald et al (2019), the fractional bias for the years 1990 to 2010 was −0.18, −0.02, and 0.22 for the wet deposition of reduced nitrogen, oxidised nitrogen, and SO 2− 4 respectively, but the overall overestimation of SO 2− 4 was mainly caused by an overestimation in the first years of the period. Running the EMEP model in global mode, Ge et al (2021) showed that the model captures the overall spatial and seasonal variations well for the major inorganic pollutants NH 3 , NO 2 , SO 2 , HNO 3 , NH + 4 , NO − 3 , and SO 2− 4 and wet depositions in East Asia, Southeast Asia, Europe, and North America.…”
Section: Model Descriptionmentioning
confidence: 99%
“…For the trend studies presented in Theobald et al (2019), the fractional bias for the years 1990 to 2010 was −0.18, −0.02, and 0.22 for the wet deposition of reduced nitrogen, oxidised nitrogen, and SO 2− 4 respectively, but the overall overestimation of SO 2− 4 was mainly caused by an overestimation in the first years of the period. Running the EMEP model in global mode, Ge et al (2021) showed that the model captures the overall spatial and seasonal variations well for the major inorganic pollutants NH 3 , NO 2 , SO 2 , HNO 3 , NH + 4 , NO − 3 , and SO 2− 4 and wet depositions in East Asia, Southeast Asia, Europe, and North America.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The WRF 110 simulation in this work assimilates data of the numerical weather prediction model meteorological reanalysis from the US National Center for Environmental Prediction (NCEP)/National Center for Atmospheric Research (NCAR) Global Forecast System (GFS) (Saha et al, 2010). The global EMEP-WRF configurations are detailed in Ge et al (2021).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The lowest model layer has height ~50 m and surface concentrations of most species were adjusted to correspond to 3 m above the surface as described in Simpson et al (2012;. Ge et al (2021) document a comprehensive evaluation of surface concentrations and wet deposition of Nr and Sr species from this model configuration against global measurements.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that pollution processes in the atmospheric environment are very complex, including air-pollutant generation, transport, chemical transformation, decomposition, and deposition. However, most studies focus on common atmospheric pollutants, such as PM, O 3 , NO 2 , SO 2 , and CO. As an important sink of atmospheric pollutants, deposition pollution has seldom been predicted or estimated by applying ML models, and the common simulation method for deposition has been numerical models such as the global 3-D model from the Goddard Earth Observing System (GEOS), GEOS-Chem [113], and the chemical transport model developed at Meteorological Synthesizing Centre-West (MSC-W) from the European Monitoring and Evaluation Programme (EMEP), the EMEP MSC-W chemical transport model [114].…”
Section: Case Study: ML Application To Nitrate Wet Deposition Estimationmentioning
confidence: 99%